Let f : R → R be a continuous function :
f ( x ) = ∫ 0 x f ( t ) d t .
Find f ( ln 5 ) .
This is a part of 10-seconds challenge .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yes, exactly! You got it! (+1)
I would omit the passage "Now since we know (1) represents an exponential equation which is always greater than 0"; it's not correct and not needed for your argument: f ( x ) = C e x together with f ( 0 ) = 0 does the job.
Log in to reply
Thanks for helping.. Yet again ;-)
This solution is incorrect. From f ′ ( x ) = f ( x ) you cannot infer that f ( x ) = e x + C .
We could write f ( x ) = C e x ... but do we need to justify why that works?
Log in to reply
No... f ( x ) f ′ ( x ) = 1 Integrating both sides ln ( f ( x ) ) = x + C ⟹ f ( x ) = e x + C Isn't it correct?? Edit:- Its the same thing you have let e C as another constant!!
Log in to reply
There is a flaw in each step: You are dividing by 0 and then you are taking the ln of 0.
The proper way to do this kind of problem is by Integrating Factors
Log in to reply
@Otto Bretscher – Thanks.. I'll delete my solution..:-)
Log in to reply
@Rishabh Jain – Write a better one! You can do it!
Put x = 0 , clearly we get f ( 0 ) = 0
Now differentiate on both sides, we get
f ′ ( x ) = f ( x )
Now, f ( x ) f ′ ( x ) = 1
Now, integrate ∫ f ( x ) f ′ ( x ) d x = ∫ 1 d x
⇒ ln ( f ( x ) ) = x + C
Where C is the constant of integration
We get, f ( x ) = e x + C ⇒ f ( 0 ) = e 0 + C ⇒ e C = 0
Therefore, f ( x ) = e x e C = e x ( 0 ) = 0
Hence, f ( ln 5 ) = 0
Problem Loading...
Note Loading...
Set Loading...
Differentiating both sides:- f ′ ( x ) = f ( x ) Multiplying by e − x on both sides:- e − x f ′ ( x ) − e − x f ( x ) = 0 d x d ( e − x f ( x ) ) = 0 ⟹ e − x f ( x ) = C For some real constant C . ⟹ f ( x ) = C e x ⋯ ( 1 ) Putting x = 0 in the given condition (i.e f ( x ) = ∫ 0 x f ( t ) d t ), we get f ( 0 ) = 0 ⋯ ( 2 ) . From 1 and 2 :- f ( x ) = 0 ∀ x ∈ R Hence, f ( ln 5 ) = 0